2022
DOI: 10.1039/d2ee00663d
|View full text |Cite
|
Sign up to set email alerts
|

The high open-circuit voltage of perovskite solar cells: a review

Abstract: Perovskite solar cells (PSCs) have made incredibly fast progress in past years, pushing the efficiency approaching 26%, which is comparable to the best silicon solar cells. One of the features...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
194
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(200 citation statements)
references
References 344 publications
(492 reference statements)
4
194
2
Order By: Relevance
“…Besides, it has been reported that Sn(II) induced defects, including heavily self‐doping of Sn 2+ to Sn 4+ , tin‐rich environment‐induced Sn(I) antisite defects (Sn I ), and iodide vacancies (V I ), represent formidable factors for the huge open‐circuit voltage loss ( V oc,loss ) and poor device performance of tin‐based PSCs. [ 21,22 ] Therefore, effective strategies that mitigate Sn(II)‐induced defects are essential for high‐performance devices. Previous studies have demonstrated that appropriate functional additive can effectively suppress Sn 2+ oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been reported that Sn(II) induced defects, including heavily self‐doping of Sn 2+ to Sn 4+ , tin‐rich environment‐induced Sn(I) antisite defects (Sn I ), and iodide vacancies (V I ), represent formidable factors for the huge open‐circuit voltage loss ( V oc,loss ) and poor device performance of tin‐based PSCs. [ 21,22 ] Therefore, effective strategies that mitigate Sn(II)‐induced defects are essential for high‐performance devices. Previous studies have demonstrated that appropriate functional additive can effectively suppress Sn 2+ oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Although power conversion efficiency (PCE) of over 20% has been achieved, [ 2 ] the efficiency of CsPbX 3 solar cells still lags behind their hybrid perovskite counterparts, essentially because of the large open‐circuit voltage ( V OC ) deficits ( E g / q − V OC ). [ 2d,3 ] Hybrid PSCs working with high efficiencies show V OC deficits of 0.3–0.4 V while CsPbX 3 solar cells always suffer from much larger deficits (0.5–0.7 V). For example, a formamidinium (FA) based hybrid PSC working with a PCE of 25.2% ( E g = 1.56 eV, V OC = 1.19 V) shows only 0.37 V deficit, [ 4 ] and a recently reported triple‐cation hybrid perovskite‐based PSC ( E g = 1.51 eV, V OC = 1.12 V) exhibits V OC deficit of 0.32 V. [ 5 ] While a CsPbI 3 perovskite‐based PSC working with high efficiency of 20.08% ( E g ≈ 1.70 eV, V OC = 1.15 V) shows a V OC deficit of 0.55 V. [ 2a ] Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…The defects are always positively or negatively charged species that can trap/localize electrons or holes respectively, causing nonradiative recombination. [ 3 ] For reducing the bulk defects, in the early stage, many processes such as stepwise annealing, [ 9 ] additive engineering, [ 10 ] and film growth atmosphere controlling [ 11 ] were developed to make high‐quality CsPbX 3 perovskite film. With continuous efforts, high‐quality light absorber film with monolayered grains has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[28] In details, the minimal V oc loss of CsPbBr 3 PSCs is 0.598 V, which is much higher than 0.3 V for FAPbI 3 PSCs, 0.34 V for MAPbI 3 PSCs, 0.44 V for Cs 0.17 FA 0.83 Pb(I 0.4 Br 0.6 ) 3 PSCs, 0.38 V for CsPbI 3 PSCs and other lower bandgap PSCs. [29][30][31][32][33][34][35][36][37] Considering that the serious V oc loss is highly related to the defects in perovskite film, it is understandable that there are more defects in CsPbBr 3 film than that of other films. Therefore, it is advantageous to reveal the relationship between defect and crystal plane by studying CsPbBr 3 solar cell.…”
Section: Introductionmentioning
confidence: 99%